Passive Energy Strategies for Mediterranean Residential Buildings Facing the Challenges of Climate Change and Vulnerable Populations - Monge-Barrio, Aurora (Green Energy and Technology,, 2018)
This book presents an approach to energy-efficient building design, which takes into account the most important challenges in climate change mitigation and adaptation in Southern Europe. It outlines a specific approach related to residential buildings and their intergenerational and vulnerable occupants, such as ageing population and users in fuel poverty. It also focuses on the use of passive energy measures throughout the year, and on pursuing a realistic and affordable approach to the efficient rehabilitation of resilient residential buildings. In addition, the book presents case studies that include surveys, monitoring, and simulation of residential buildings in Spain and other Southern European representative locations, in order to go further on the study of this challenging topic.